Investigation of Effects of Local Vitamin C Application on Inflammatory Response and Periodontal Tissue Destruction in Rat Periodontitis Model - Kübra Karaçam; Ayşe Toraman; Zeliha Aytekin (Selcuk Dental Journal)
Background: The present study aims to evaluate the effect of local vitamin C application on inflammatory response and periodontal tissue destruction in rats with experimental periodontitis. Methods: A total of 21 animals, 7 rats in each group, were used in the study: 1- Non-ligation (NL), 2-experimental periodontitis (EP), and 3- local vitamin C (VtC) groups. Experimental periodontitis was induced in EP and VtC group rats. After 11 days, the ligature was removed. 50 mL of saline solution and vitamin C were injected locally into the vestibule sulcus of the EP and VtC group rats, respectively. After the rats were sacrificed, blood and gingival tissue samples were taken. TNF-α levels were analyzed biochemically in serum and 8-OHdG and MMP-8 were analyzed immunohistochemically in gingival tissue. The mandibular specimens were histologically evaluated for bone destruction and attachment loss. Results: The numeric density of 8-OHdG and MMP-8 immunopositive cells were found to be statistically significantly lower in the Vtc group than in the EP group. Vitamin C administration significantly reduced attachment loss and bone loss in the VtC group as compared to the EP group. However, there was no significant difference in serum TNF-α level in the VtC group compared to the EP group. Conclusions: Local application of vitamin C may reduce inflammation-related bone destruction by supporting the inflammatory response with the antioxidant activity of vitamin C and contributing to the resolution of inflammation with its potential immunomodulatory effect. Vitamin C may be a therapeutic agent that can be used in the treatment of periodontitis.